Origin of the Zika virus revealed: a historical journey across the world. (21st September 2016) - Mlacker, Stephanie; Shafa, Golsa; Aldahan, Adam S.; Shah, Vidhi V.; Samarkandy, Sahal; Nouri, Keyvan
Abstract: Background: Zika virus (ZIKV) is an arbovirus within the Flaviviridae family, the recent spread of which has promoted public concern. Methods: This study outlines the clinical features, potential for teratogenicity, diagnosis, and treatment of ZIKV infection. Results: Zika virus is transmitted through the bite of an infected Stegomyia (= Aedes ) mosquito, blood transfusion, sexual intercourse, and perinatal routes. Infection has been characterized as mildly symptomatic. Symptoms include mild fever, headache, arthralgia, myalgia, non‐purulent conjunctivitis, and a pruritic maculopapular rash. It is rarely life‐threatening, but both Guillain–Barré syndrome and fetal microcephaly have been reported. ZIKV belongs to the same family as bovine viral diarrhea virus, which causes hydrocephalus and microcephaly in newborn calves, and hepatitis C virus, which can be vertically transmitted in human pregnancies, and hence there remains concern for potential similarities. Diagnostic methods include polymerase chain reaction performed in blood samples during infection, and in urine and saliva. Pregnant women undergo antibody testing for immunoglobulin M. Treatment involves supportive care, and acetaminophen and antihistamines to control symptoms. Conclusions: Although there was no evidence of the circulation of ZIKV in the Western hemisphere prior to 2014, the global spread of Stegomyia aegypti and increases in urban populations and international travel have fostered its evolution. Adherence to current guidelines for the prevention of ZIKV transmission is especially relevant in regions experiencing ongoing outbreaks. Concern for microcephaly in newborns warrants further investigation into the potential long‐term effects of ZIKV infection, especially in relation to reproductive health and mother–fetus transmission.